A Vision Among Challenges: Lessons About Online Teaching From The First Online Master’s Degree in Digital Sociology - Tressie M. Cottom; Jennifer A. Johnson; Tara M. Stamm; Julie Honnold (Journal of Public and Professional Sociology)
According to data from an American Sociological Association survey, just half of all degree-granting sociology departments in the academic year 2012-2013 offered at least one “distance learning course in sociology” (Spalter-Roth, Van Vooren & Kisielewski, 2013). Two years after this report was released, Virginia Commonwealth University’s Department of Sociology (VCU SOCY) launched the first online master’s of science degree in digital sociology in a climate where distance learning could not yet be considered hegemonic in U.S. sociology programs. In launching the program, VCU SOCY attended to several documented trends in online learning at sociology departments. First, the degree program exists in the same “market model” (Brint, Proctor, Murphy, Hanneman, 2012) mentioned in the ASA report. This a macro context that is shaping all manner of educational expansion and stratification. This market model attaches various forms of status (Tuchman, 2009) and economic resources to creating revenue-generating degree programs. Second, the degree program is part of a trend in model diversification that aims to serve the new “traditional” college student, i.e. not a straight-from-high-school undergraduate student. By 2014, the majority of all college students were what we would have once called “non-traditional”, making schedule flexibility the new norm for colleges that want to grow enrollment, prestige or market share. Third, this new master’s of science program was responding to growing disciplinary interest in digitally-mediated societies and social processes. In this paper we explore how these three trends impacted the design and implementation of online teaching in an online graduate sociology program. We find that market models incentivize departments and faculty to develop online courses but resource uptake is uneven. We also find uneven success with online educational materials and tools when the focus is on graduate students as opposed to undergraduate students. And, we find that new online teaching models might be best suited for bleeding edge disciplinary innovations because the union of new models of teaching and new models of thinking have natural synergies.